Effect of Curcuma Longa Rhizome Extract on Fasting Blood Sugar Levels and HbA1C in Type 2 Diabetes Mellitus: A Meta-Analysis - Fatony, Riska Fajar; Tamtomo, Didik Gunawan; Prasetya, Hanung (Masters Program in Public Health, Sebelas Maret University, 2021)
Background: Diabetes mellitus (DM) is a metabolic disease that is developing into a serious global problem. Diabetes mellitus is characterized by an increase in blood levels that are more than the normal reference. In type 2 DM generally occurs due to reduced insulin secretion and sensitivity over time. Control of blood sugar levels can improve the patient's quality of life. This study aimed to analyze the effect of curcuma longa rhizome extract on fasting blood sugar levels and HbA1C in patients with type 2 diabetes.Subjects and Method: This was a meta-analysis of a number of randomized controlled trials. The articles were obtained from PubMed, Google Scholar, Springerlink, BMJ, and Sciencedirect databases, published from 2010-2020. The article search was carried out by considering the eligibility criteria defined using the PICO model. P: Type 2 diabetes patients, I: Curcuma longa rhizome extract, C: Placebo, and O: Fasting blood sugar levels and HbA1C. The keywords to find articles are as follows: